African iron working, between durability of knowledge and diversity of technogy - (:unkn) unknown (My University, 2016)
Iron production has played a part in the history of Africa for more than 2,500 years. The study of this specific human activity has demonstrated its exceptional significance, its historical continuity and an astonishing variability of practice. In sub-Saharan Africa, metallurgists have developed different ways to produce the same material: iron. They have multiplied the technical choices to a degree unequalled on other continents. In Africa, only the bloomery process has been used, but dozens of variants of this process have been developed. This diversity has long enabled research to compare the techniques used, reconstruct changes in techniques over time, and examine population settlement patterns. Several analytic systems have tried to characterize the variants and to understand their presence: Why are there so many methods to make iron?In this paper, we see, via different examples, the factors that caused diversity in African iron smelting. First of all, we begin with the material constraints and the adaptations of the metallurgists. Next, we examine the link between the diversity of iron traditions and the identity of metallurgists. Certain similarity between traditions perhaps reflects the transmission of knowledge and mechanisms by which technologies are learnt. The scale of production also has an impact on the bloomery process. We will see that certain iron traditions may support intensive production. We conclude with thoughts on possible distinctions between culture, economic context and population dynamics to explain the extreme variability in African ironworking and on possible future researches to better understand this question.
Keywords: African Research